2010
DOI: 10.1007/s00359-010-0522-8
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of liquid epicuticular hydrocarbons and tarsal adhesive secretion in Leptinotarsa decemlineata Say (Coleoptera: Chrysomelidae)

Abstract: Species of various insect orders possess specialised tarsal adhesive structures covered by a thin liquid film, which is deposited in the form of footprints. This adhesive liquid has been suggested to be chemically and physiologically related to the epicuticular lipid layer, which naturally covers the body of insects and acts as the prime barrier to environmental stresses, such as desiccation. The functional efficiency of the layer, however, is jeopardised by partial melting that may occur at physiological temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 56 publications
3
43
1
Order By: Relevance
“…On a physiological level, the CHC layer experiences two basic selection pressures: firstly, its melting point must be high enough to waterproof the insect cuticle at ambient temperatures. Secondly, it must be fluid enough so that substances relevant for nest-mate recognition and/or waterproofing can spread over the cuticle [3,35] and be exchanged among nest-mates.…”
Section: Discussionmentioning
confidence: 99%
“…On a physiological level, the CHC layer experiences two basic selection pressures: firstly, its melting point must be high enough to waterproof the insect cuticle at ambient temperatures. Secondly, it must be fluid enough so that substances relevant for nest-mate recognition and/or waterproofing can spread over the cuticle [3,35] and be exchanged among nest-mates.…”
Section: Discussionmentioning
confidence: 99%
“…To enable adhesion, insect feet are inherently 'tacky', employing an adhesive fluid secretion to maximise contact with a substrate (Gorb, 2005;Pohl and Beutel, 2004). The exact composition of the secretion is still unknown, although there is a general acknowledgement that it is an emulsion of lipophilic and hydrophilic components (Votsch et al, 2002), but no hydrophilic liquid has been identified (Geiselhardt et al, 2010). Indeed, Dirks and colleagues state that hydrophobic fluids stick well to both hydrophobic and hydrophilic surfaces (Dirks et al, 2009), and the inclusion of a hydrophilic component to the adhesive secretion used by insects has unclear benefits.…”
Section: Introductionmentioning
confidence: 99%
“…A chemical congruence of tarsal and cuticular lipids, therefore, would be expected in these beetle species. In contrast, the species included in the present study are equipped with specialised attachment structures and at least some possess glands, which seem to be involved in the secretion of the adhesive liquid (SF Geiselhardt et al 2010). Hence, the locally restricted production of a specialised formula with optimised adhesive properties would be physiologically possible.…”
Section: Resultsmentioning
confidence: 92%
“…In the present study, we have chosen a representative selection of mostly plant-inhabiting beetles, in which all possess widened tarsal segments and adhesive hairs (Stork 1980;own observations), presumably connected to specialised glandular cells (Betz 2003;SF Geiselhardt et al 2010). Our focus is on the Chrysomeloidea and Curculionoidea (29 species), where broadened tarsi and adhesive devices seem to be a ubiquitous character that may have evolved in adaptation to life on smooth plant surfaces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation